FENOMENA HIJRAH DI KALANGAN SELEBRITIS: ANALISIS TEORI RATIONAL CHOICE DAN TEORI KONSTRUKSI SOSIAL - Ahmad Musadad; Mochamad Syaifudin; Tri Pujiati; Fajar; Baihaqi (Qolamuna : Jurnal Studi Islam, 2025)
The phenomenon of hijrah among Indonesian celebrities has attracted public and media attention. This research aims to analyse the phenomenon with Rational Choice theory and Social Construction theory. This research methodology uses a descriptive qualitativeapproach. Research informants include celebrities who have made hijrah, religious experts, and social observers. Data were collected through observation and documentation studies. Data analysis was conducted using thematic analysis techniques to identify key themes related to the motivation and impact of hijrah. The results showed that celebrities' hijrah decisions were influenced by rational considerations, such as the search for a deeper meaning of life, social pressure, and the desire to change public image. In addition, the hijrah process is also influenced by social construction formed through interaction with religiouscommunities and support from followers on social media. This study concludes that the celebrity hijrah phenomenon is the result of a combination of rational choice and social construction. The contribution of this research is to provide a new perspective inunderstanding social and religious dynamics among celebrities. Research recommendations include the need for further studies on the role of social media in the hijrah process and its impact on fans. Keywords: Celebrity hijrah, rational choice, social construction, social media, religious dynamics